Avaliação dos efeitos de um programa para ensinar professores a conduzir uma etapa de uma análise de contingências: o levantamento da provável função do comportamento - Cerqueira, Daniele Maria Oliveira de (2009)
The analysis of contingencies of reinforcement has been considered the basic tool of behavior analysts. When conducting an analysis of contingencies, the behavior analyst seeks to identify relationships between behavior and aspects of the environment, using functional units of behavior as their object of study. Different authors have considered that procedures to assess functional characteristics of behavior are powerful tools to identify contingencies of reinforcement that maintain behavioral disorders and to develop effective intervention programs. Considering the importance of applying an analysis of contingencies in the school context in order to seek solutions to problems of behavior displayed by students in the classroom, this study aimed to train teachers to identify the likely role of the student's behavior which is considered inadequate. Three preschool teachers of private school participated in the study. The phases that composed the procedure were: baseline, training (workshop and a procedure of removal of information with seven steps) and post-test. Moreover, a question was applied, in order to verify generalization, in which the teachers should identify the function of the misconduct of a student in their classes as well as propose an appropriate intervention for the behavior of the student. The procedure of removal of information included 64 scenarios showing situations in the classroom in which students' inappropriate behavior occurred, together with the antecedent events and the consequences of such behavior and with information on what happened to the frequency of behavior with the passage of time. The behavior could have one of two functions: to attract the attention of the teacher (positive reinforcement) or to escape from academic tasks (negative reinforcement). Each scenario was accompanied by questions about different aspects to be considered in the analysis of contingencies, which were initially accompanied by the replies supplied by the experimenter, which were gradually removed so that the participants then answered the questions. The results showed that the participants properly identified the probable function of behavior, both in the post-test scenarios and the test of generalization. Despite identifying the function of the behavior of their students in the test of generalization, two of the participants were not able to propose an appropriate intervention to change the behavior of the student. The results lead to the conclusion that the proposed training was effective in teaching teachers to identify the probable function of the behavior of the student